Pelatihan Manajemen Web untuk Peningkatan Promosi pada KUD Tani Makmur Kecamatan Kasihan - Setia Wardani; Yulian Agus Suminar (Universitas Serang Raya, 2018)
The purpose of Community Service (PPM) in KUD Tani Makmur Kasihan, among others, first: to help employees KUD Tani Makmur to understand web based promotion management, second: improve motivation and creativity KUD Tani Makmur employee that the constraints of the facilities is not a reason to learn and forward, and third: provide an overview to employees of KUD Tani Makmur how to promote products in the virtual world so that its products can be recognized by other regions. The method used by PPM Training of Web Usage for Promotion Management Improvement at KUD Tani Makmur Kasihan, among others, held lectures and discussions, held training / workshop and evaluation. PPM Targets Web-Use Training for Promotion Management Improvement among others KUD Tani Makmur Kasihan helps employees of KUD Tani Makmur Kasihan District to be able to use the web to improve information and promotion of KUD Tani Makmur Kasihan.